Analisis Nilai Pengukuran Penerangan pada Laboratorium Ergonomi sesuai Permenaker No 05 Tahun 2018 - Aulia Nadia Rachmat; Mochamad Yusuf Santoso; Ricky Zakaria (G-Tech: Jurnal Teknologi Terapan, 2023)
The ergonomics laboratory is one of the facilities of vocational education at the diploma level. The ergonomics laboratory is used for various practical activities, including anthropometric data measurement, work sampling, and biomechanics. This activity is required in accordance with the standards. So, this study will discuss the measurement and analysis of lighting in the room in agreement with SNI 7062: 2019 and Permenaker No. 05 of 2018. The ergonomics laboratory is divided into 3 rooms, namely the technician room, the lecturer room, and the main laboratory. The results of the measurement of the average lighting intensity in the ergonomics laboratory are 101.23, 136.63 lux, and 161.58 lux. The three rooms do not meet the lighting standards. Several factors that influence this condition include the presence of a square window in this room which is covered by building components so that it blocks sunlight as natural lighting from entering room.